TREATMENT OF CHRONIC MIGRAINE WITH INFILTRATIONS AND SPHENOPALATINE BLOCK: CASE REPORT - Hayak Pereira Lopes, Maykon (Health and Society, 2025)
Chronic migraine is a debilitating condition that affects millions of people globally, significantly impacting patients’ quality of life and productivity. This case report describes the management of a 42-year-old woman diagnosed with chronic migraine for 20 years, with no relevant comorbidities. The patient experienced 20 monthly episodes of mild pain and 4 of severe pain. Treatment included trigger point infiltrations with a solution of 0.25% levobupivacaine, 25% glucose, and 6.5 mg of dexamethasone, totaling 10 mL, and nasal sphenopalatine block with the same solution. Pharmacological treatment was supplemented with atenolol 25 mg daily. The infiltration and sphenopalatine block protocol was repeated after 21 days. After three months, a significant reduction in the frequency and intensity of attacks was observed, suggesting that the combination of infiltrations and pharmacological therapy is an effective strategy in the management of chronic migraine.